Influence of discipline on employee performance in regional disaster management agency kota Sungai Penuh - Hairoman Hairoman (Jurnal Aplikasi IPTEK Indonesia, 2018)
This study aims to determine the effect of discipline on the performance of employees at the Regional Disaster Management Agency of Sungai Penuh City, to know the amount of influence discipline on the performance of employees at the Regional Disaster Management Agency of Sungai Penuh City. This type of research is quantitative research to see the influence between independent variables (independent) with dependent variable (dependent). In this study the researcher wanted to see the effect of discipline on the performance of employees at the Regional Disaster Management Agency of Sungai Penuh City. The results of this study are: obtained Ha value received on the significance and ? (0.05)> 0.05 (significikacy) means there is a significant effect of discipline on the performance of employees at the Regional Disaster Management Agency of Sungai Penuh City. then the better the discipline the better the performance of employees. The influence of discipline on the performance of employees At the Regional Disaster Management Agency in kota  Sungai Penuh city City is influenced by factors other than discipline.